2021
DOI: 10.1038/s41390-021-01521-7
|View full text |Cite
|
Sign up to set email alerts
|

Neuroplacentology in congenital heart disease: placental connections to neurodevelopmental outcomes

Abstract: Children with congenital heart disease (CHD) are living longer due to effective medical and surgical management. However, the majority have neurodevelopmental delays or disorders. The role of the placenta in fetal brain development is unclear and is the focus of an emerging field known as neuroplacentology. In this review, we summarize neurodevelopmental outcomes in CHD and their brain imaging correlates both in utero and postnatally. We review differences in the structure and function of the placenta in pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 126 publications
(134 reference statements)
3
26
0
3
Order By: Relevance
“…The adaptive cerebral vasodilation in the fetus with CHD results in a lower MCA PI, which may or may not be accompanied by placental insufficiency (130)(131)(132)(133)(134). Higher rates of placental pathologies are known to occur in pregnancies complicated by fetal CHD (135)(136)(137)(138)(139), therefore CPR requires careful interpretation in fetuses with CHD.…”
Section: Fetal Chdmentioning
confidence: 99%
“…The adaptive cerebral vasodilation in the fetus with CHD results in a lower MCA PI, which may or may not be accompanied by placental insufficiency (130)(131)(132)(133)(134). Higher rates of placental pathologies are known to occur in pregnancies complicated by fetal CHD (135)(136)(137)(138)(139), therefore CPR requires careful interpretation in fetuses with CHD.…”
Section: Fetal Chdmentioning
confidence: 99%
“…Fetuses with CHDs are more vulnerable to a hypoxic environment, so there is increased importance in antenatal and postnatal development for CHD fetuses with placental malperfusion. 38 39 This study can contribute to improving prenatal detection of CHD by selecting high risk mothers with maternal serum markers for aneuploidy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, higher pBOLD temporal variance could correspond to a less cohesive hemodynamic response among the various placental cotyledons in CHD compared to non-CHD. This could explain varying response times of CHD placentas to hyperoxygenation stimulus 42 . Differences in spatial variance, seen in Figure 2, based on CHD status, may correspond to the prevalence of regional vascular impairments in each of the cotelydons.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, recent histopathological evidence has reported that placentas, in CHD, show a spectrum of pathological structural adaptations such as infarctions, chorangiosis, thrombosis and hypomature villi, suggesting vascular-related vulnerability and have been linked to the presence of postnatal brain injury, particularly in left ventricular outflow track obstruction heart lesion subtypes [7-11]. While these placental pathologies have been shown to correlate with newborn outcomes such as birthweight[8] and acquired postnatal brain injury, few direct associations have been found between placental abnormalities and neurodevelopmental outcomes in CHD.…”
Section: Introductionmentioning
confidence: 99%